Impacts of climate change on fishersˊ livelihood in Kishoregonj haor region, Bangladesh - Islam, Ariful; Hossain, Md Saddam; Hossain, Zakir (Asian Journal of Medical and Biological Research, 2020)
Kishoreganjhaor region is highly sensitive to the climatic events such as flash flood, soil erosion, heavy rainfall, drought, storm surge etc. The aim of this research is to assess the impacts of climate change on fishersˊ livelihoods of Kishorganjhaor region, Bangladesh. The fisherˊ livelihood data were collected through semi-structured questionnaire interview and Focused Group Discussion (FGD) method. In Kishoreganjhaor region, natural disasters have increased due to climate change, that threat on fishersˊ livelihood by extinction of fish species, low fish availability, destructing houses and other infrastructures. In the present study, it was found that 65% fishers were involved in permanent fishing activity and 35% fishers were temporarily involved in fishing with other occupation as daily labour, net making etc. A very few empirical research on the impacts of climate change in Kishoreganjhaor has been conducted, so researcher and policy makers can get information about the concern by this study and implement policy for the climate change induced affected people of the Kishoreganjhaor. Asian J. Med. Biol. Res. September 2020, 6(3): 408-417